The measurement of crime: victim reporting and police recording - Catalano, Shannan Michelle (Criminal justice, 2006)
Victim reporting and police recording -- The two measures of crime. The uniform crime reports. The national crime victimization survey. NCVS and UCR comparability. Counting and definitions between the NCVS and UCR -- Explaining the convergence. Changes in policing. Changes in population characteristics. Changes in the perception of crime. Changes in methodological design. Methodological change in the UCR. Methodological change in the NCVS -- Potential factors contributing to convergence. Disaggregated NCVS measures. Dependent variables. Explanatory variables. Demographic variables. Social attitudes. Design changes -- Hypotheses and analysis. Hypotheses. Analytic strategy. Stage one analysis. Stage two analysis -- The NCVS and UCR convergence. Summary of findings. Limitations and future research. Conclusion